5PSQ-064 Related risk of biologic drugs for Crohn's disease in pregnancy: a case report and revision of the literature. (24th March 2020) - Lucatelli, MV; Roperti, M; Bacci, C; Camuffo, L; Puzziferri, R; Pieri, G
Abstract : Background and importance: Adalimumab is a human recombinant monoclonal antibody that is increasingly used in clinical practice for induction of remission in Crohn's disease. It reduces inflammation by binding with tumour necrosis factor (TNFα) so that it cannot interact with its own receptors. Crohn disease has a peak incidence in youth. Patient fertility can be influenced depending on the stage of disease (active or remission phase). There are insufficient data about how adalimumab impacts on fertility and its safety when administered in pregnancy. Aim and objectives: This case report presents a serious adverse reaction in a 33-year-old woman treated with adalimumab during pregnancy. Material and methods: Data were extrapolated from computerised medical records. Results: In 2009, the patient was diagnosed with Crohn ileitis, which required ileocaecal resection (removal of 35 cm of ileus, 7 cm of colon and the appendix). The morphological finding was compatible with the anamnesis: active and stenosing Crohn's disease. Several drugs were prescribed: mesalamine, corticosteroids and azathioprine, although without remission. In 2010, biological therapy with adalimumab was introduced and was interrupted three times: once for pregnancy and twice for relief of symptoms, which then regressed. The patient was in clinical, endoscopic and bio-humoral remission and had been receiving adalimumab since October 2018. On the last follow-up, June 2019, the drug was interrupted: the patient was pregnant and abnormalities were identified in the morphological assessment. On 12 June, a clinician reported an adverse drug event. The morphological scan performed around the 21st week of pregnancy showed a small ectasia of the fetus's right ureter with a slight increase in right kidney dimensions. At the first scan, there were no problems identified with the fetus and so the patient continued therapy with adalimumab. The biological drug was interrupted on the 24th week of pregnancy. The seriousness of the adverse reaction will be reassessed at the next check-up. Conclusion and relevance: For adalimumab, as for other drugs, limited clinical data are available for exposed pregnancies. A toxicity study conducted in monkeys showed no indication of maternal toxicity, embryotoxicity or teratogenicity. Pharmacovigilance is essential in monitoring the safety of drugs in clinical practice, especially in populations not included in clinical trials. References and/or acknowledgements: No conflict of interest.